IMPLEMENTASI PROJECT BASED LEARNING BERBASIS LITERASI DALAM PEMBELAJARAN MENULIS TEKS NARASI DI KELAS X SMA NEGERI 3 BONE - A. Nurhabibi Marwil; Muhammad Asdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of literacy-based Project Based Learning (PjBL) in teaching narrative text writing to tenth-grade students at SMA Negeri 3 Bone.The research employed a descriptive qualitative approach to comprehensively portray the processes of planning, implementation, and evaluation of learning (Creswell & Creswell, 2018). The research subjects consisted of one Indonesian language teacher and 32 tenth-grade students selected purposively.Data were collected through observation, interviews, and documentation, and were analyzed interactively through data reduction, data display, and conclusion drawing (Miles et al., 2014). The implementation of PjBL followed the project-based learning syntax, including determining essential questions, project planning, implementation, and evaluation of outcomes (Thomas, 2000). Literacy integration was carried out through activities such as reading model texts, analyzing narrative structures, group discussions, and written reflections before and after the writing process.The findings indicate an increase in students’ active engagement during the learning process as well as improvement in the quality of the narrative text structures produced. Most students were able to organize orientation, complication, and resolution systematically with better cohesion and coherence (Dalman, 2018). However, challenges were still identified in the mechanical aspects of language, such as spelling and vocabulary variation. Overall, literacy-based PjBL effectively enhances the quality of narrative writing instruction and can serve as a strategic alternative for strengthening literacy culture at the senior high school level.